Material didáctico con estilo kawaii para el aprendizaje en el Ámbito de Relaciones Lógico Matemáticas, de estudiantes de inicial 2, de la Unidad Educativa “Víctor Sergio Ron Vega”. - Mecias Mayalica, Shirley Tatiana (2025)
The project entitled “Kawaii-Style Teaching Material for Logical-Mathematical Learning in Initial 2 Students at Víctor Sergio Ron Vega Educational Unit” arises from the need to innovate pedagogical resources in early childhood education. Within the Ecuadorian context, the scarce availability of attractive visual materials makes it difficult to capture attention, foster motivation, and develop logical thinking in children aged 4 to 5 years. The study proposes the design of teaching material in the kawaii style aimed at strengthening logical-mathematical learning through playful and interactive resources. A qualitative, descriptive, and projective approach was adopted, following Robert Scott’s methodology, which includes the following stages: identification of the need, creative process, material selection, and design production. The population consisted of 25 children and one teacher. Data were gathered through interviews, questionnaires, direct observation, and graphic recording sheets to examine visual preferences and classroom dynamics. The findings reveal that traditional materials fail to maintain children’s attention. In contrast, the new design—characterized by vibrant colors, soft shapes, and endearing characters—significantly enhances motivation and comprehension. Three educational games were developed to promote counting, classification, and the understanding of the number-quantity relationship. The kawaii style fosters emotional connection and meaningful learning, establishing itself as an innovative tool for early childhood education.